Morphology and DNA barcodes of two species of Bradysia Winnertz from China (Diptera, Sciaridae), with the description of Bradysia minorlobus Yang, Shi & Huang sp. n. - Yang, Xue; Shi, Kai; Heller, Kai; Menzel, Frank; Huang, Junhao; Wu, Hong (Zootaxa, 2019)
Two morphologically similar species of the fungicola species group of Bradysia Winnertz, 1867 were studied in China: Bradysia chenjinae Yang, Zhang & Yang, 1993 and Bradysia minorlobus Yang, Shi & Huang sp. n. The morphological species concepts were supported by the DNA barcodes of COI sequences. The genetic distances of 16 Bradysia fungicola group species were analyzed and a neighbor-joining tree was constructed. The morphological characters of both Chinese species were described and illustrated.